Implementasi Nilai-Nilai Kebangsaan dalam Menangkal Disinformasi di Era Digital: Upaya Memperkuat Demokrasi, Kesamaan Derajat, dan Ketaatan Hukum Menuju Indonesia Emas 2045 - Dani Setiadarma; Laili Fitriyah; Tri Satria Muhammad; Ferdi Setiawan (Indo Publishing, 2026)
The advancement of digital technology has accelerated the flow of information but has also increased the spread of disinformation, which threatens democracy, equality, adherence to the rule of law, and national resilience. This conceptual, literature-based article aims to analyze the implementation of national values ​​derived from the 1945 Constitution of the Republic of Indonesia as a strategy to counter disinformation in the pursuit of